Invigoration Increased Quality and Storability of True Seed of Shallot (Allium ascalonicum L.) - Adhinugraha, Qudus Sabha; Widajati, Eny; Palupi, Endah Retno (Department of Agronomy and Horticulture, IPB University, 2022)
Seed invigoration is a pre-planting seed treatment by balancing the seed water potential and stimulating their metabolic activities so that the seeds germinate simultaneously. In this study, invigoration treatments were applied to improve the quality of the true seeds of shallots (TSS) that had started to deteriorate. Invigoration increases the moisture content of the seeds so the seeds need to be re-dried to extend their storability. The aims of the study were to determine the best invigoration treatment and the drying method to maintain the benefit of invigoration, and to prolong TSS storability after invigoration and drying. This research was conducted at the Laboratory of Seed Quality Testing, IPB University, Indonesia, and consisted of three experiments, i.e., invigoration of deteriorating TSS to improve their viability and vigor, drying after invigoration to extend seed storability, and seed storability after invigoration and drying treatments. The first experiment was arranged in completely randomized design with one-factor (invigoration solutions), i.e. control, medium containing 3% KNO3, 50 ppm GA3, 0.5 % ZnSO4 or PEG6000 -10 bar. The second experiment was conducted using a two-factor completely randomized design, drying temperature (20˚C, 30˚C, and 40˚C), and drying duration (8 hours, 16 hours, 32 hours, and 48 hours). The third experiment was arranged in a nested design with two factors. The first factor was a seed storage condition, i.e., ambient temperature, air-conditioned room, and refrigerator. The second factor was seed packages, i.e., aluminum foil and polypropylene plastic. Non-invigorated seeds were used as control. The studies were conducted on two shallot varieties separately, “Trisula” and “Lokananta”, except in the third experiment which only used “Lokananta”. The results showed that invigoration in 3 % KNO3 and 50 ppm GA3 effectively improved the vigor of deteriorating TSS. Drying the seeds at 40˚C for 8 hours was the most effective method to reduce seed moisture content without reducing the benefit of invigoration. Storing the invigorated TSS in an air-conditioned room with aluminum foil packaging, or in a refrigerator with aluminum foil or plastic packaging until 14 weeks maintained the benefit of invigoration. The quality of the invigorated TSS was maintained until 14 weeks in an air-conditioned room with aluminum foil packaging, or in a refrigerator with aluminum